Fuzzy Robust H∞ Tracking Control For Wind Generator System: LMI approach - Lahmadi, Kaoutar; Boumhidi, Ismail (Transactions on Engineering and Computing Sciences, 2017)
This study concerns the tracking control problem of the wind turbine generator system with uncertainties parameters and external disturbances. Based on T-S fuzzy model, a fuzzy observer-based and a fuzzy robust state feedback output tracking control are developed to reduce the tracking error by minimizing the disturbance level caused by the wind speed. Using a Lyapunov function combined with H∞ tracking criteria and a judicious of the famous Young relation, a sufficient stability condition for the robust fuzzy tracking control formulated in terms of linear matrix inequality, which can be very efficiently solved by using LMI optimization techniques. The simulation results are given to show the performance of the observer-based tracking controller.